Candida albicans : cellular and molecular biology - Prasad, R. 1947- (Springer, 2017)
This book on Candida albicans and similar pathogens provides a timely overview of the groundbreaking discoveries made in the areas of drug resistance, host pathogen interactions, virulence, host immune system modulation, etc., in the last two decades. This comprehensive 2nd Edition includes chapters on fungal infections, hyphal morphogenesis, molecular mechanisms of antifungal resistance, antifungal agents, multidrug transporters, virulence mechanisms in Candida albicans, host pathogen interactions, the cell wall, fungal biofilms, lipids and antifungal resistance, signaling mechanisms and last but not the least host-immune responses. As such, it offers an ideal reference guide for mycologists, researchers, pharmacists, clinicians, and undergraduate students engaged or interested in fungal research. It will also benefit clinicians, who are required to keep abreast of the current state of research on antifungal drug resistance and antifungal development.
Keywords: Candida albicans.; elektronické knihy; electronic books